Building the Croatian Dependency Treebank: the initial stages - Tadić, Marko (2007)
The paper presents the work-in-progress of building the Croatian Dependency Treebank. Its design principles, procedures and the pilot corpus used within are described. Perspectives for further development of the Croatian Dependency Treebank are presented at the end.
Projekt MZOS
Projekt MZOS
ENG